Penerapan Metode K-Nearest Neighbor Untuk Pemilihan Rekomendasi Game FPS Pada Aplikasi Google Play Store - Puji Pangestu; Resad Setyadi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Game or game is a recreational activity with the aim of having fun, hobbies and free time. Games or games are usually done alone or together. Electronic games or better known as virtual games are games that use electronic media, which is entertainment in the form of multimedia that is made as attractive as possible so that players can get something so that there is inner satisfaction. Many game lovers are enthusiastic about the development of the game industry, including FPS games. FPS stands for